High-Level Serum Fibroblast Growth Factor 21 Concentration Is Closely Associated With an Increased Risk of Cardiovascular Diseases: A Systematic Review and Meta-Analysis - Zhang, Yucong; Yan, Jinhua; Yang, Ni; Qian, Zonghao; Nie, Hao; Yang, Zhen; Yan, Dan; Wei, Xiuxian; Ruan, Lei; Huang, Yi; Zhang, Cuntai; Zhang, Le (Frontiers in Cardiovascular Medicine, 2021)
Background: The association between fibroblast growth factor 21 (FGF21) and cardiovascular diseases (CVDs) risk remains unclear. We conducted this systematic review and meta-analysis to evaluate the association between FGF21 and CVDs, and relevant vascular parameters. Methods: PubMed and Web of Science databases were systematically searched to identify relevant studies published before March, 2021. The FGF21 concentration was compared between individuals with or without CVDs. The effect of FGF21 on CVDs risk was assessed by using hazard ratio (HR) and odds ratio (OR). The association between FGF21 and vascular parameters was assessed by Pearson’s r. Study quality was assessed using Newcastle-Ottawa Scale and Joanna Briggs Institution Checklist. Results: A total of 29156 individuals from 30 studies were included. Overall, the serum FGF21 concentration was significantly higher in CVDs patients (p<0.001), especially for coronary artery disease (CAD) (p<0.001) and hypertension (p<0.001). The pooled OR (p=0.009) and HR (p<0.001) showed that the risk of CVDs increased with FGF21. The linear association between FGF21 and vascular parameters, including pulse wave velocity (r=0.32), carotid intima-media thickness (r=0.21), ankle-brachial index (r=0.33), systolic blood pressure (r=0.13) and diastolic blood pressure (r=0.05), was insignificant. The incidence of overall CVDs (p=0.03) was significantly higher in individuals with higher FGF21 levels. Conclusion: High-level serum FGF21 concentration is closely associated with an increased risk of CVDs, which may be independent of vascular parameters. A standard FGF21 classification threshold needs to be established before clinical use for CVD risk assessment.